AKUNTABILITAS, TRANSPARANSI, DAN PENERAPAN STANDAR AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN ETIKA SEBAGAI VARIABEL MODERASI - Kamelia; Lince Bulutoding; Sapril Sardi Juardi (Universitas Islam Negeri Alauddin Makassar, 2024)
Abstract, This study aims to examine the effect of accountability, transparency and the application of accounting standards on the quality of financial statements. In addition, this study also examines whether ethics can moderate the relationship between accountability, transparency, and the application of accounting standards to the quality of financial statements. This research is quantitative research with a descriptive approach. The population in this study were employees who worked in the Enrekang Regency Regional Work Unit with purposive sampling technique. The results of multiple linear analysis show that accountability and the application of accounting standards have a positive and significant effect on the quality of financial statements. While transparency has a negative effect on the quality of financial statements on the quality of financial statements. The moderating variable, namely ethics, is able to moderate accountability on the quality of financial statements while ethics are not able to moderate transparency and the application of accounting standards to the quality of financial statements. The implication of this research is that in an effort to improve the quality of financial statements, organizations must pay special attention to the level of accountability and the application of accounting standards. Keywords: Accountability, transparency, the application of accounting standards, ethics, and the quality of financial statements